The role of post-translational modifications in parvovirus life cycle - Liu, Peng; Yang, Liqin (Frontiers in Veterinary Science, 2025)
Parvoviruses are a group of single-stranded DNA viruses that lack an envelope and are widely distributed in both vertebrates and invertebrates. When they infect a host cell, parvoviruses take over the cell’s translational machinery to support the viral genome replication and proteins synthesis, following which viral proteins undergo various post-translational modifications (PTMs). Parvovirus non-structural (NS) and capsid proteins are modified by PTMs, including phosphorylation, ubiquitination, SUMOylation, and glycosylation. Phosphorylation of parvovirus mainly occurs on NS and capsid proteins, modulating the functions and activities of the NS protein and the assembly of the capsid protein. Ubiquitination and SUMOylation of parvoviral capsid proteins mainly affect intracellular trafficking during viral infection. Glycosylation of parvoviral capsid proteins is involved in the regulation of virion stability and infectivity. In this review, we summarize the PTMs of parvovirus proteins and discuss their impact on the viral life cycle, which will help in understanding viral replication and pathogenesis.